2015
DOI: 10.1177/0269216315575841
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring the benefits of hospital admissions from the perspectives of patients with palliative care needs

Abstract: Background: The acute hospital plays a significant role in caring for people with a life-limiting illness. Most research to date has focused exclusively upon the negative aspects of hospitalisation. Currently, there is little known about the benefits of hospital admissions for patients with palliative care needs. Aim: The aim of this study was to explore the benefits of hospital admissions, from the perspectives of patients with palliative care needs. Design: A qualitative study design was adopted. Longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 43 publications
(65 reference statements)
1
42
0
1
Order By: Relevance
“…However, there is clear evidence indicating that preferences may change as a person’s circumstances evolve. Indeed, the closer to death people come, the less likely they will be to choose death at home and in fact many will choose a hospital setting [ 35 , 36 ]. Moreover, while ‘home’ is commonly understood to be a fixed geographical location, research has shown that home is in fact a malleable concept [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is clear evidence indicating that preferences may change as a person’s circumstances evolve. Indeed, the closer to death people come, the less likely they will be to choose death at home and in fact many will choose a hospital setting [ 35 , 36 ]. Moreover, while ‘home’ is commonly understood to be a fixed geographical location, research has shown that home is in fact a malleable concept [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, whilst people rarely choose the hospital as their preferred place of care at the end of life [ 40 ], the hospital may become an attractive refuge during periods of acute illness. For example, patients with palliative care needs admitted to hospital during a period of acute illness have described feeling safe and cared for while being monitored and observed by health professionals with knowledge and expertise about their illness [ 36 ]. This suggests that when care needs are changing home may feel less safe than inpatient settings.…”
Section: Discussionmentioning
confidence: 99%
“…However, we know far too little about the patient’s view of palliative care. Just a handful of studies have been published in this field, and these were focused on the preferred place of death, communication, and the influence of cultural backgrounds [ 3 , 11 17 ]. Patients’ preferences in palliative care revealed four key aspects: living a meaningful life, responsive health care personnel and care environment, and responsiveness in the organization of palliative care [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with incurable lung diseases lack understanding of their condition and knowledge about the dynamics of COPD or similar fatal diseases and the possibility of dying from this disease, as well as patient education and reassurance of appropriate symptom management (e.g. to prevent sensation of suffocation) are well-accepted measures to help these patients [13]. Eligibility criteria for palliative care units and hospices can be found in Table 1.…”
Section: Conduct Future Talks!mentioning
confidence: 99%